ANALISIS PENERAPAN PERHITUNGAN TAX PLANNING DENGAN METODE NET DAN METODE GROSS UP TERHADAP PPH BADAN - Mahwiyah Mahwiyah (Keberlanjutan : Jurnal Manajemen dan Jurnal Akuntansi, 2018)
AbstractThe purpose of this study was to determine whether there is a comparison between the calculation of the net method and the tax gross-up method (income tax) body transform and minimize the tax owed. The method of analysis used descriptive qualitative method, in which the author takes the data relating to Income Tax Article 21, including the recap salary then analyze the components in question are salary and benefits.  After doing the analysis, it can be concluded that the presence of Tax Planning is the company can do a comparison of income tax (VAT) of Article 21 by using Method Net or Gross-up method is the most efficient method is to gross-up or giving an allowance of tax payable, from the comparison of the two calculations are done, the gross-up method or allowances payable for the tax efficiency of the Income Tax (VAT) amounting Rp3.141.683 Agency for 2010, Rp1.513.929 for 2011, and Rp1.846.733 for 2012. Keywords: Article 21 Income Tax,   Corporate Income Tax, Net Methods and Gross Up Method